The impact of online classes on sleep, physical activity, and cognition functioning among physical education students - Haddad, Monoem; Abbes, Zied; Abdel-Salam, Abdel-Salam G. (Frontiers in Psychology, 2024)
Introduction Online education has become a crucial component of teachers’ professional development, and universities incorporate innovative pedagogical approaches to enhance teachers’ training. These approaches have proven invaluable, particularly during the COVID-19 pandemic. This study investigates the impact of online versus face-to-face learning environments on sleep quality, physical activity, and cognitive functioning among physical education students. Methods Utilizing a unique methodological approach that combines wrist actigraphy, the Pittsburgh Sleep Quality Index, and the Cambridge Neuropsychological Test Automated Battery, we provide a comprehensive assessment of these variables. Over 4 weeks, 19 male students participated in alternating online and face-to-face class formats. Results Our results reveal no significant differences in sleep quality or cognitive function between learning environments. However, notable findings include significant differences in Paired Associates Learning and weekday step counts in the face-to-face setting. Discussion These insights suggest that while online learning environments may not adversely affect sleep or cognitive functions, they could impact certain aspects of physical activity and specific cognitive tasks. These findings contribute to the nuanced understanding of online learning’s implications and can inform the design of educational strategies that promote student well-being.